2016
DOI: 10.1007/s12185-016-1996-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-dose methotrexate in combination with tacrolimus was associated with rapid engraftment and recovery from oral mucositis without affecting the incidence of GVHD

Abstract: Allogeneic hematopoietic stem cell transplantation is a curable treatment for hematological diseases. Graft-versus-host disease (GVHD) causes morbidity and mortality after HSCT.Methotrexate (MTX) is used for GVHD prophylaxis, but its appropriate dose remains unclear. In the present study, we compared the efficacy and toxicity of 15-10-10 MTX (day +1: 15 mg/m 2 ; days +3 and +6: 10 mg/m 2 ) with 10-7-7 MTX (day +1: 10 mg/m 2 ; day +3and +6: 7 mg/m 2 ) in combination with tacrolimus. The cumulative incidences ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Timely insertion and proliferation of stem cells in neutrophil and thrombocyte engraftments are essential in reducing risk and severity of OM. Earlier studies have reported at length on the relationship between neutrophil engraftment and OM, and the positive correlation has also been confirmed between the duration of mucositis and neutrophil engraftment 19 . Reduced as opposed to standard dose MTX in allogeneic HSCT patients resulted in shorter neutrophil engraftment time and faster recovery from mucositis 19 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Timely insertion and proliferation of stem cells in neutrophil and thrombocyte engraftments are essential in reducing risk and severity of OM. Earlier studies have reported at length on the relationship between neutrophil engraftment and OM, and the positive correlation has also been confirmed between the duration of mucositis and neutrophil engraftment 19 . Reduced as opposed to standard dose MTX in allogeneic HSCT patients resulted in shorter neutrophil engraftment time and faster recovery from mucositis 19 .…”
Section: Discussionmentioning
confidence: 59%
“…Earlier studies have reported at length on the relationship between neutrophil engraftment and OM, and the positive correlation has also been confirmed between the duration of mucositis and neutrophil engraftment 19 . Reduced as opposed to standard dose MTX in allogeneic HSCT patients resulted in shorter neutrophil engraftment time and faster recovery from mucositis 19 . The anti-inflammatory, antioxidant and wound-healing promoting effects of erythropoietin containing mouthwash in patients who underwent APSCT, reducing severity and incidence of OM without significant effect on blood neutrophil and thrombocyte engraftment 12 , further supports the role of local factors in the aetiology and therapy of OM.…”
Section: Discussionmentioning
confidence: 59%
“…The use of MTX as immunoprophylaxis may also have been a contributing factor to OM high incidence due to its high cytotoxic potential in cells with rapid multiplication. In addition, MTX is responsible for the delay of repair of the tissue damaged by chemotherapeutic conditioning (Ahmed et al, 2017;Cutler et al, 2005;Knoll et al, 2016;Matsukawa et al, 2016;Ramírez-amador et al, 2010;Small et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Efficient engraftment occurs through three steps: i) migration of infused HSCs toward bone marrow microvessels through adhesion molecules and their expression on the surface of endothelial cells; ii) stem cells homing to the bone marrow niche via interactions with homing receptors; iii) proliferation and differentiation of HSCs to various blood cells 5 . Many factors may influence the kinetics of engraftment after allo‐HSCT, including the number of HSCs and T cells, subset of T cells, infections, graft‐versus‐host disease (GVHD) prophylaxis, post‐transplant granulocyte colony‐stimulating factor (G‐CSF) administration, and the disease status 4,6‐8 . Cancer therapy‐related neutropenia is the most common complication resulting from chemotherapy toxicity 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 Many factors may influence the kinetics of engraftment after allo‐HSCT, including the number of HSCs and T cells, subset of T cells, infections, graft‐versus‐host disease (GVHD) prophylaxis, post‐transplant granulocyte colony‐stimulating factor (G‐CSF) administration, and the disease status. 4 , 6 , 7 , 8 Cancer therapy‐related neutropenia is the most common complication resulting from chemotherapy toxicity. 9 Before the HSCT, patients receive high‐dose chemotherapy regimens, which have myelosuppressive effects.…”
Section: Introductionmentioning
confidence: 99%